2011
DOI: 10.1155/2011/360805
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Responses Induced by a Fungal BiopesticideMetarhizium anisopliaeand House Dust Mite Are Compared in a Mouse Model

Abstract: Biopesticides can be effective in controlling their target pest. However, research regarding allergenicity and asthma development is limited. We compared the ability of fungal biopesticide Metarhizium anisopliae (MACA) and house dust mite (HDM) extracts to induce allergic responses in BALB/c mice. The extracts were administered by intratracheal aspiration at doubling doses (2.5–80 μg protein) 4X over a four-week period. Three days after the last exposure, serum and bronchoalveolar lavage fluid (BALF) were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Nevertheless, the importance of exposure time, the potential of different fungal species and molecular components responsible for damage and symptoms are still unknown. A common mechanism associated with allergy triggered by biocontrol agents such as B. bassiana (Westwood et al, 2005 , 2006 ), Metarhizium anisopliae (Ward et al, 2011 ), Paecilomyces and Trichoderma viride (Beezhold et al, 2008 ), and Penicillium oxalicum (Kochar et al, 2014 ) is the production of IgE against fungal molecules observed in animal models and human patients.…”
Section: Biocontrol Agents and Immune System Homeostasismentioning
confidence: 99%
“…Nevertheless, the importance of exposure time, the potential of different fungal species and molecular components responsible for damage and symptoms are still unknown. A common mechanism associated with allergy triggered by biocontrol agents such as B. bassiana (Westwood et al, 2005 , 2006 ), Metarhizium anisopliae (Ward et al, 2011 ), Paecilomyces and Trichoderma viride (Beezhold et al, 2008 ), and Penicillium oxalicum (Kochar et al, 2014 ) is the production of IgE against fungal molecules observed in animal models and human patients.…”
Section: Biocontrol Agents and Immune System Homeostasismentioning
confidence: 99%